2024
DOI: 10.1037/edu0000830
|View full text |Cite
|
Sign up to set email alerts
|

Reading comprehension on handheld devices versus on paper: A narrative review and meta-analysis of the medium effect and its moderators.

Ladislao Salmerón,
Lidia Altamura,
Pablo Delgado
et al.

Abstract: As handheld devices, such as tablets, become a common tool in schools, a critical and urgent question for the research community is to assess their potential impact on educational outcomes. Previous meta-analytic research has evidenced the "screen inferiority effect": Readers tend to understand texts slightly worse when reading on-screen than when reading the same text in print. Most primary studies from those metaanalyses used computers as on-screen reading devices. Accordingly, the extent to which handheld d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…It is possible that the medium used to read misinformation and corrections would affect how both are processed. Multiple research syntheses have concluded that readers remember and understand informational text better on paper than on screens (Clinton, 2019;Delgado et al, 2018;Kong et al, 2018;Salmerón et al, 2023). This is thought to be due to the shallowing hypothesis in which screens are associated with quick, enjoyable tasks with low cognitive demand (Annisette & Lafreniere, 2017;Delgado & Salmerón, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is possible that the medium used to read misinformation and corrections would affect how both are processed. Multiple research syntheses have concluded that readers remember and understand informational text better on paper than on screens (Clinton, 2019;Delgado et al, 2018;Kong et al, 2018;Salmerón et al, 2023). This is thought to be due to the shallowing hypothesis in which screens are associated with quick, enjoyable tasks with low cognitive demand (Annisette & Lafreniere, 2017;Delgado & Salmerón, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effects of text genre (expository or narrative) are also mixed; for instance, Mangen et al [ 29 ] observed a comprehension advantage for print over digital media for both narrative and expository texts, whereas others have shown that reading narrative texts yields similar comprehension outcomes regardless of the medium [ 1 , 2 , 30 ]. However, in a recent meta-analysis, Salmerón et al [ 4 ] showed that level of comprehension (textual and inferential) was not moderated by text genre (narrative or expository), whether the texts were read on a tablet/computer or paper.…”
Section: Introductionmentioning
confidence: 99%
“…The use of digital platforms for delivery of instruction and information at school and at home is now requisite for students at all levels, from elementary school through higher education. The increased use of digital materials alongside paper-based materials in learning environments has motivated research into the efficacy of reading and learning in one format versus the other (e.g., [1][2][3][4]), and although there is an overall finding for a paper-based advantage, the outcomes have been characterized by small effect sizes and variability associated with participant, stimulus, and task factors (e.g., [5,6]). Some reports have indicated no differences between print and digital media with respect to story understanding or comprehension measures [7][8][9][10], or test scores [11].…”
Section: Introductionmentioning
confidence: 99%